REASONS AND CONSEQUENCES OF CHANGING ELECTORAL SYSTEMS IN UKRAINE - Зінченко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article analyzes the development of electoral systems in Ukraine in the context of changing electoral law. It is shown that each new parliament adopts a new bill, which changes the rules for holding the next election, taking into consideration the realities, the political schedule of forces and the experience of holding the past elections. The inability of MPs to create and approve an optimal electoral system in Ukraine is shown.